2021
DOI: 10.1021/acsaem.1c00689
|View full text |Cite
|
Sign up to set email alerts
|

ZnCl2 as a “Nitrogen Bank” to Inhibit Nitrogen Loss during the Thermal Conversion of Nitrogen-Containing Carbon Precursors to Nitrogen-Doped Carbon

Abstract: A universal synthesis strategy for inhibiting the nitrogen loss during the thermal conversion of N-containing carbon precursors to nitrogen-doped carbon is developed. ZnCl2, as a sacrificial additive in the pyrolysis, acts like a “nitrogen bank” (“N-bank”) to accommodate the N-containing intermediates from the decomposed precursors and redopes the nitrogen back into the final carbon materials. The nitrogen-doped carbon synthesized by this N-bank synthesis strategy has a significantly elevated nitrogen content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…ZnCl 2 can create wide micropores and small mesopores during activation, which promotes the migration of electrolyte ions (Martin et al, 1996). Moreover, Su et al found that ZnCl 2 as a sacri cial additive, could play the role of a N-bank during the thermal conversion of nitrogen-containing carbon precursors to nitrogen-doped carbon, which can sequester nitrogen in nitrogen-containing precursors and signi cantly inhibit nitrogen loss (Su et al, 2021). Therefore, ZnCl 2 will be selected as an activator in this work because of its good pore-forming ability and nitrogen xation function.…”
Section: Introductionmentioning
confidence: 99%
“…ZnCl 2 can create wide micropores and small mesopores during activation, which promotes the migration of electrolyte ions (Martin et al, 1996). Moreover, Su et al found that ZnCl 2 as a sacri cial additive, could play the role of a N-bank during the thermal conversion of nitrogen-containing carbon precursors to nitrogen-doped carbon, which can sequester nitrogen in nitrogen-containing precursors and signi cantly inhibit nitrogen loss (Su et al, 2021). Therefore, ZnCl 2 will be selected as an activator in this work because of its good pore-forming ability and nitrogen xation function.…”
Section: Introductionmentioning
confidence: 99%
“…Most methods for introducing nitrogen functionalities into or onto carbon require high temperatures, for example, chemical vapor deposition, 13 carbonization of N-containing carbon-based polymers, 14 pyrolysis of carbon- and nitrogen-containing precursors, 15 and arc-discharge from graphite electrodes. 16 As stated above, these methods are generally not successful in selecting for one nitrogen bonding environment over another.…”
Section: Introductionmentioning
confidence: 99%
“…and oxidative acids (HNO 3 , H 2 SO 4 , H 3 PO 4 ). [74][75][76][77][78][79][80][81][82][83][84] Among them, KOH is the most powerful activation agent and the activation mechanism can be expressed as outlined below:…”
Section: Introductionmentioning
confidence: 99%
“…and oxidative acids (HNO 3 , H 2 SO 4 , H 3 PO 4 ). 74–84 Among them, KOH is the most powerful activation agent and the activation mechanism can be expressed as outlined below: 11 6KOH + 2C → 2K + 3H 2 + 2K 2 CO 3 K + KOH → K 2 O + H 2 K 2 O + CO 2 → K 2 CO 3 K 2 CO 3 + 2C → 2K + 3COK 2 O + C → 2K + CO…”
Section: Introductionmentioning
confidence: 99%